A civilizational change: decoloniality, transdiplomacy, and norm localization - Tinoco Blacio, Fergie; Vázquez Hidalgo, María Dolores (El Outsider: Journal of International Relations and Political Science, 2022)
Superiority and hegemony based on reasoning, economics, and eurocentrism as a permanent precept has been established by states and societies; in consequence, other philosophies, from Asian and Indigenous cultures, are deemed not applicable and capable of fulfilling the "objectives'' of all individuals. This conception's legitimacy has led to ignoring the "Other" and disregarding their wisdom; however, the “other” has remained latent by the localization of globalized norms to indigenous worldview. From a critical point of view, this paper analyzes the civilizational change made by indigenous actors to the generalized social norms of the West. It is affirmed that the Andean worldview has remained in social action through localized norms that have made it possible to resolve issues from non-traditional and collectivist perspectives. It has been silently co-opted by prioritizing Western philosophy.
Keywords: indigenism; co-option; Western world; power; invisibility; localization; counter-hegemony; international relations